Needs Analysis for Designing and Developing a Traditional Games Application to Enhance Psychomotor and Cognitive Skills in Inclusive Elementary Education - Setyawan, Feri Budi; Priambadha, Aprida Agung; Sofyan, Iyan; Susanto, Bahtiyar Heru; Rohani, Nanda; Astuti, Dinda Tri; Chun, Adelbertus Chun (Journal of Teaching and Learning, 2026)
Inclusive elementary education increasingly emphasizes the development of both psychomotor and cognitive skills among students with diverse learning needs. However, existing instructional approaches often rely on conventional strategies that fail to meet the dynamic requirements of inclusive classrooms. Although traditional games are culturally rooted and pedagogically rich, their integration into digital learning tools remains limited, particularly in enhancing specific skill domains such as motor coordination, memory, logical reasoning, and adaptive Journal of Teaching and Learning 20(2) F. Setyawan, A. Priambadha, I. Sofyan, B. Susanto, N. Rohani, D. Astuti, & A. Chun Chun 75 interaction. A critical gap exists in the design of educational applications that adapt traditional gameplay for inclusive use while aligning with differentiated instructional needs. This needs-analysis study is guided by a conceptual framework that integrates inclusive education principles and game-based learning, emphasizing learner-centred engagement, differentiated instruction, and the pedagogical potential of games. Using a sequential mixed-methods approach, data were collected via a closed-ended questionnaire and focus group discussions with 15 inclusive elementary school teachers in Yogyakarta, Indonesia. The questionnaire covered four dimensions: instructional relevance, user accessibility, pedagogical suitability, and digital integration. Findings revealed strong support for incorporating traditional games to engage learners across ability levels, but raised concerns about limited access to assistive features, a lack of digital infrastructure, and insufficient teacher preparedness for using game-based applications. Participants also stressed the need for customizable content, culturally responsive game mechanics, and sensory-sensitive design features to ensure meaningful inclusion. These findings provide critical insights for future development of inclusive educational technologies and emphasize the value of stakeholderinformed design in bridging pedagogical and technological priorities.